PENGARUH KUALITAS PELAYANAN MICE TERHADAP KEPUASAN PELANGGAN DI F - I Made Rahmadi Putra; Ni Luh Gde Sri Sadjuni; Ni Desak Made Santi Diwyarthi (JURNAL BISNIS HOSPITALITI, 2026)
Customer satisfaction is a key factor in the success of hotels in organizing MICE (Meetings, Incentives, Conferences, and Exhibitions) events. This satisfaction is achieved when employees provide services that meet the needs and expectations of MICE customers. Based on the event feedback form at FP Hotel Bali, the service scored the lowest, indicating the need for an improvement in service quality. This study aims to analyze the influence of MICE service quality on customer satisfaction at FP Hotel Bali. Data were obtained through questionnaires distributed to 88 respondents using simple random sampling and a Likert scale. Data analysis techniques included simple linear regression, the coefficient of determination, and the T-test. The results showed that MICE service quality has a positive and significant effect on customer satisfaction. The T-test indicated that the t-value of 10.492 was greater than the t-table value of 1.663, and the significance value of 0.001 was less than 0.05, meaning Ha was accepted and H0 was rejected. Based on the analysis of the coefficient of determination, MICE service quality has a very strong influence of 83.7% on customer satisfaction, while the remaining 16.3% is influenced by other variables not examined